2014
DOI: 10.1002/bmb.20829
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and genetic analysis of an environmental bacteriophage: A 10‐session laboratory series in molecular virology

Abstract: Bacterial viruses, otherwise known as bacteriophage (or phage), are some of the most abundant viruses found in the environment. They can be easily isolated from water or soil and are ideal for use in laboratory classrooms due to their ease of culture and inherent safety. Here, we describe a series of 10 laboratory exercises where students collect, isolate, and purify the genome of an environmental phage. Once the genome has been extracted, students then clone a fragment of their isolated phage genome into a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Perturbation of HeLa (i.e., human fibroblast cells) and broad monitoring of the cells' proteome by SDS-polyacrylamide electrophoresis was done with a single, class-chosen environmental stimulus [20]. PCR and subcloning of bacteriophage genomic DNA fragments is part of a semester-long, molecular virology project [22]. PCR and subcloning of bacteriophage genomic DNA fragments is part of a semester-long, molecular virology project [22].…”
Section: Resultsmentioning
confidence: 99%
“…Perturbation of HeLa (i.e., human fibroblast cells) and broad monitoring of the cells' proteome by SDS-polyacrylamide electrophoresis was done with a single, class-chosen environmental stimulus [20]. PCR and subcloning of bacteriophage genomic DNA fragments is part of a semester-long, molecular virology project [22]. PCR and subcloning of bacteriophage genomic DNA fragments is part of a semester-long, molecular virology project [22].…”
Section: Resultsmentioning
confidence: 99%
“…In order to increase the scientific literacy of non-STEM (science, technology, engineering, and mathematics) majors and to enhance their understanding of the scientific process, the SEA-PHAGES program has been successfully offered as a two-semester nonmajors course (33). And finally, similar to PHIRE/SEA-PHAGES, Williamson et al (34) reported a series of 10 lab exercises for isolation and purification of an environmental phage; students attempt to clone a fragment of the genomic DNA and sequence it to attempt to identify the phage.…”
Section: Labmentioning
confidence: 99%
“…Bacteria and their viruses (“bacteriophages” or “phages”) grow quickly, are easy to work with, and are relatively inexpensive. Due to these low resource requirements, laboratory exercises where students isolate phages are already becoming more prevalent in undergraduate biology programs, which led the way for our modified high school module (Jordan et al, 2014; Williamson et al, 2014). Here we present a weeklong, in-class activity where students at Lincoln Southwest High School (LSW) work with instructors from Michigan State University (MSU) to utilize scientific practices to “hunt” for bacteriophages.…”
Section: Introductionmentioning
confidence: 99%